2019
DOI: 10.2147/ijn.s195828
|View full text |Cite
|
Sign up to set email alerts
|

<p>PEGylated and CD47-conjugated nanoellipsoidal artificial antigen-presenting cells minimize phagocytosis and augment anti-tumor T-cell responses</p>

Abstract: Purpose: Antigen-presenting cells (APCs) are powerful tools to expand antigen-specific T cells ex vivo and in vivo for tumor immunotherapy, but suffer from time-consuming generation and biosafety concerns raised by live cells. Alternatively, the cell-free artificial antigen-presenting cells (aAPCs) have been rapidly developed. Nanoscale aAPCs are recently proposed owing to their superior biodistribution and reduced embolism than conventional cell-sized aAPCs, but pose the challenges: easier cellular uptake and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 42 publications
0
28
0
Order By: Relevance
“…Various works have also reported conferring “stealth” properties to nanomaterials by attachment of surface molecules such as polyethylene glycol (PEG) ( Suk et al, 2016 ) and CD47 molecules ( Gheibi Hayat et al, 2019 ) to prolong their systemic circulation time by delaying in vivo clearance ( Fam et al, 2020 ). A recent study on the fabrication of nano-artificial antigen-presenting cells (aAPCs) decorated with both PEG and CD47 moieties have shown evasion of nanoparticles to phagocytic clearance along with their ability to induce the generation of antigen-specific T cells to suppress tumour development ( Song et al, 2019 ). Another promising feature of NMs towards drug delivery applications is the ability to easily functionalize their surfaces with various ligands to improve cellular uptake and achieve a highly specific targeted drug delivery ( Cisterna et al, 2016 ; Sykes et al, 2016 ).…”
Section: Mechanism Of Immunomodulation By Nanomaterialsmentioning
confidence: 99%
“…Various works have also reported conferring “stealth” properties to nanomaterials by attachment of surface molecules such as polyethylene glycol (PEG) ( Suk et al, 2016 ) and CD47 molecules ( Gheibi Hayat et al, 2019 ) to prolong their systemic circulation time by delaying in vivo clearance ( Fam et al, 2020 ). A recent study on the fabrication of nano-artificial antigen-presenting cells (aAPCs) decorated with both PEG and CD47 moieties have shown evasion of nanoparticles to phagocytic clearance along with their ability to induce the generation of antigen-specific T cells to suppress tumour development ( Song et al, 2019 ). Another promising feature of NMs towards drug delivery applications is the ability to easily functionalize their surfaces with various ligands to improve cellular uptake and achieve a highly specific targeted drug delivery ( Cisterna et al, 2016 ; Sykes et al, 2016 ).…”
Section: Mechanism Of Immunomodulation By Nanomaterialsmentioning
confidence: 99%
“…They found that the co-loaded NP gave superior phagocytic capabilities compared to individual drug treatments and minimal effects from the free drug at later timepoints. Additionally, CD47-coated NPs can act as stealth coatings, taking advantage of CD47 as a marker of self ( Qie et al, 2016 ; Song et al, 2019 ). Qie et al modified the surface of polystyrene beads with polyethylene glycol or CD47 and found CD47 is able to lower the phagocytic activity of classically activated macrophages ( Qie et al, 2016 ).…”
Section: “Don’t Eat Me” Signals: Cd47 Beta-2-microglobulin and Cd24mentioning
confidence: 99%
“…For brevity, the first two items will be explained. APC as an important tool for expansion of antigen-specific T cells has been exploring its artificial modality to address the low-yielding problem in ACT [54,165]. Nano-aAPCs as a biomimetic platform presented three signals on the surface to stepwisely accomplish antigen presentation, co-stimulation and cytokine release, which are not only used ex vivo for T-cell expansion but also in vivo for antigen-specific CD8 + T cell activation, synergizing with the development of cancer immunotherapy [166].…”
Section: Adoptive Cell Therapymentioning
confidence: 99%
“…Ellipsoidal nano-aAPCs with excellent pharmacokinetic characteristics have better stretching ability while reducing non-specific cellular uptake when compared to spherical nano-aAPCs [167]. A new "stealth" ellipsoidal nano-aAPC, which had been PEGylated and conjugated with self-marker CD47-Fc, was fabricated to further reduce intracellular absorption and enhance expansion capacity of T cells [54]. Noteworthily, aAPCs that produced by lipid bilayers on various cell-templated silica microparticles suggested that scaffolds' size, shape, rigidity, antigen density and antibody loading ratio all exert influence on the ability of antigen-specific T-cell expansion, so the optimal nano-APCs need to be evaluated by multiple parameters and multiple platforms [168].…”
Section: Adoptive Cell Therapymentioning
confidence: 99%